Temperature-dependent oxygen utilization rates of the mesopelagic water in the Southeast Asian basins - Liu, Zhiqing; Huang, Peng (Frontiers in Marine Science, 2025)
IntroductionThe Southeast Asian Seas (SEAS), characterized by interconnected basins separated by shallow sills, serve as a critical pathway for the Indonesian throughflow (ITF), regulating Indo-Pacific climate and biogeochemical exchanges. While temperature is a key driver of marine oxygen balance, its influence on mesopelagic oxygen dynamics in the SEAS remains underexplored.MethodsWe integrated age estimation using transient tracers with the Arrhenius equation to explore temperature-dependent oxygen consumption processes. The apparent activation energy (Ea) was computed to quantify the temperature sensitivity. The oxygen utilization rate (OUR) was measured at various depths within the mesopelagic zone.ResultsBy combining the age estimation based on transient tracer with the Arrhenius equation, this study investigates temperature-dependent oxygen consumption processes in the SEAS mesopelagic zone (200–1000 m), revealing an average apparent activation energy (Ea) of 100.9kJ mol-1. There is a robust positive correlation (R2 > 0.64) between the oxygen utilization rate (OUR) and temperature in the mesopelagic, which is consistent with fundamental biochemical kinetics. A significant disparity in Ea was observed between the western (126.8 kJ mol-1) and eastern (89.8 kJ mol-1) ITF pathways, attributed to contrasting water masses from the North and South Pacific.DiscussionThe combination of temperature and organic matter can explain these regional differences. The stratified results show that a strong linear relationship still exists in the 200–600 m. However, a deviation from the classical Arrhenius equation was observed in the 600–1000 m, where physical processes such as mixing and water mass transport, along with biological factors like substrate availability and microbial community composition, might modulate oxygen consumption patterns. Projected warming scenarios indicated differential responses: a 2°C temperature rise amplified oxygen consumption by 30.7% (western ITF) and 45.9% (eastern ITF), underscoring temperature as a critical modulator of future oxygen loss.